2004
DOI: 10.1159/000078174
|View full text |Cite
|
Sign up to set email alerts
|

SARS in Newborns and Children

Abstract: The severe acute respiratory syndrome (SARS) is a highly contagious infection caused by a newly discovered strain of coronavirus (SARS-CoV). Infants born to pregnant women with SARS did not appear to acquire the infection through vertical transmission. Some newborn infants, however, developed severe intrauterine growth retardation and life-threatening gastrointestinal complications. It is now known that the clinical course and prognosis are different between paediatric and adult SARS patients. Young children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 26 publications
(74 reference statements)
1
66
0
1
Order By: Relevance
“…The SARS outbreak of 2003, caused by a newly identified coronavirus, affected >8,000 persons worldwide ( 22 ). Reports suggest that the clinical course and outcomes of SARS might be more severe for pregnant than for nonpregnant women ( 23 ).…”
Section: Issues In Treatment and Prophylaxis Of Emerging Infections Amentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS outbreak of 2003, caused by a newly identified coronavirus, affected >8,000 persons worldwide ( 22 ). Reports suggest that the clinical course and outcomes of SARS might be more severe for pregnant than for nonpregnant women ( 23 ).…”
Section: Issues In Treatment and Prophylaxis Of Emerging Infections Amentioning
confidence: 99%
“…Animal studies and some human studies have demonstrated an increased risk for birth defects when corticosteroids are used during pregnancy ( 26 ). In spite of this information, all but 1 of the 12 pregnant women with SARS reported from Hong Kong Special Administrative Region, People's Republic of China Special Administrative Region, People's Republic of China received ribavirin and corticosteroid treatment ( 22 ), probably because their illness was life-threatening. On the basis of more recent data, the efficacy of ribavirin and corticosteroids in the treatment of patients with SARS has been questioned ( 24 ).…”
Section: Issues In Treatment and Prophylaxis Of Emerging Infections Amentioning
confidence: 99%
“…No clinical, radiologic, or laboratory evidence for transmission 169 from mother to fetus was observed, despite laboratory testing of different specimens. 12,13…”
mentioning
confidence: 99%
“…IgM antibodies declined after 30 days and IgG antibodies persisted up to day 210 [14] and antiviral neutralizing antibodies were obtained from convalescent patients [14]. Morbidity rates were greater for older individuals, while children under 12 years of age did not develop the severe disease that was seen in adults [15]. Taken together these data may suggest that the quality of the immune response may play a role in the outcome of virus infection.…”
Section: Immunological Features Associated With Sars-covmentioning
confidence: 89%